Low-Range Tracking Radio Altimeter with a Phase-Locked Loop - A. A. Monakov; A. A. Tarasenkov (Известия высших учебных заведений России: Радиоэлектроника, 2022)
Introduction. The article proposes a new principle for designing a low-range tracking radio altimeter based on a phase-locked loop (PLL) for frequency-modulated continuous-wave radar (FMCW) systems.Aim. To develop a model of a low-range tracking radio altimeter, which uses a PLL to estimate the height, as well as to verify its performance via computer simulation.Materials and methods. To solve the problem, we develop a mathematical model of the tracking radio altimeter with an estimator that uses the principles of PLL to generate a reference signal.Results. Computer simulation of a radio altimeter with the PLL circuit to measure the height above a rough surface proves the altitude estimate to be efficient. When operating over a perfectly flat surface, the altimeter provides an efficient altitude estimate for a signal-to-noise ratio greater than 10 dB. When operating over a rough surface under the selected scenario parameters, and the signal-to-noise ratio of 20 dB, the resulting height estimate provides a bias, with its standard deviation growing with increasing the surface roughness. When the standard deviation of the surface roughness is twice the transmission wavelength, the bias and standard deviation of the estimate equal 1 m and 5 m, respectively, under the altimeter height of 150 m. The conducted simulation revealed that the quality of the altimeter performance is subject to abnormal errors, which are caused by deep fading of the received signal due to the signal reflecting from a rough surface.Conclusion. The altimeter under study can be used for estimating the altitude of aircraft flights. Further research will investigate the effect of various factors on the performance quality of the radio altimeter, its circuit implementation and full-scale tests.